COVID‐19 is the only issue that will matter in 2021 - Hodges, Dawn Z. (Disability Compliance for Higher Education, 2021)
For 2021, there's only one issue that will matter for higher education: COVID‐19. The pandemic is impacting every aspect of higher education, including technology, curriculum, learning, grades, COVID‐19 testing, campus safety, mental health, enrollment, mergers, closures, layoffs, and fundraising.